2007
DOI: 10.1021/ma062708p
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development, and Evaluation of Monovinyl Acrylates Characterized by Secondary Functionalities as Reactive Diluents to Diacrylates

Abstract: This study focuses on the design and development of novel monovinylic (meth)acrylate monomers with enhanced polymerization kinetics and the evaluation of their performance as reactive diluents in diacrylate systems. Novel (meth)acrylic monomers characterized by several new secondary functionalities are developed in this study and are shown to exhibit reactivities 10-70 fold greater than traditional monoacrylates such as hexyl acrylate. These monomers were designed based on our understanding of interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…With the exception of the experimental specimen that contained 3 wt% TTMSS, the heights of tan δ peak for the experimental specimens were not significantly different from the control ( p < 0.05). Previous investigators have reported decreased polymerization rate and more homogenous network structure with the addition of TTMSS [64]. The current investigation shows similar results, i.e., the heterogeneity of the copolymer was decreased by the slower polymerization rate associated with an increase in the TTMSS concentration.…”
Section: Discussionsupporting
confidence: 86%
“…With the exception of the experimental specimen that contained 3 wt% TTMSS, the heights of tan δ peak for the experimental specimens were not significantly different from the control ( p < 0.05). Previous investigators have reported decreased polymerization rate and more homogenous network structure with the addition of TTMSS [64]. The current investigation shows similar results, i.e., the heterogeneity of the copolymer was decreased by the slower polymerization rate associated with an increase in the TTMSS concentration.…”
Section: Discussionsupporting
confidence: 86%
“…The carbamate functionality was chosen as a result of its predisposition towards higher reactivity than the carbonate21 as illustrated in Figures 2 and 3. The role of the cyclic carbonate moiety is then evident from comparisons with aromatic end functionalized carbamates.…”
Section: Resultsmentioning
confidence: 99%
“…A major drawback in photopolymerizable systems is the large amount of unreacted photoinitiator in the cured polymer material . Due to the high conversion rates in a very short time, only a few initiator molecules are able to covalently bind to the growing polymer network.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with exposure to radiation sources like UV‐light or sunlight, a variety of photo‐products are generated. They cause odor, volatile compounds such as benzaldehyde, yellowing of the material and migration of all byproducts out of the polymer matrix over time …”
Section: Introductionmentioning
confidence: 99%